Growing third places: A qualitative study of experiences and perceived benefits of a campus community garden as a nature-based health intervention - Olivia D’Andrea Brooks; Rubiga Thanganathan; Lesley Gittings (PLoS ONE, 2025)
This study explored the experiences and perceived health and wellbeing benefits of participating in a campus community garden among university staff, students, and faculty. Community gardens are increasingly recognized for their potential to positively impact physical, mental, and emotional health, as well as increase social connection. Their impact within university settings, specifically in Canadian post-secondary contexts, remains underexplored. This qualitative study was conducted at a large Canadian university. Fourteen participants affiliated with the campus community garden (including students, staff, and faculty) participated in semi-structured, in-depth interviews. Data were analyzed using thematic analysis. Four key themes emerged: (1) the garden as a “third place”, (2) deepened connection to nature, (3) empowerment through knowledge and ability to grow food, and (4) community building. Findings suggest that campus community gardens offer a cost-effective and accessible approach to supporting mental wellbeing, food security, and connectedness to nature in post-secondary settings. By functioning as a third place and fostering engagement with nature, campus community gardens may provide students and staff with meaningful opportunities for community integration, improved wellbeing and personal growth. These findings support integrating community gardens into campus wellness strategies and sustainability initiatives.